Influence of ABC Mix and Gibberellin on Growth and Yield of Red Rice under Soilless Cultivation - Mahindra Dewi Nur Aisyah; Ibadina Syahida, Ahya (KHD Production, 2026)
The use of AB Mix as a nutrient in soilless paddy cultivation actually prolongs the vegetative phase, which results in delayed flowering. This study aims to analyze the effects of gibberellin concentration and ABC Mix (AB Mix + silica) on flowering age, growth, and production yield of red paddy. The experiment was designed using a split plot arrangement within a completely randomized design involving 2 factors and 3 replications. The first factor was gibberellin concentration (sub plot) consisting of 2 treatments: control and 200 ppm. The second factor was ABC Mix nutrient concentration (main plot) consisting of 4 treatments: EC 750–800 ppm, EC 1,000–1,050 ppm, EC 1,250–1,300 ppm, and EC 1,500–1,550 ppm. The results showed that the ABC Mix treatment at EC 750–800 ppm combined with GA3 at 200 ppm significantly affected plant height (192.0 cm). Additionally, the GA3 200 ppm treatment also significantly influenced grain weight per clump (39.03 grams) and plant height. Meanwhile, the ABC Mix EC 750–800 ppm treatment showed significant differences in total tiller number (60.03 stalks), number of productive tillers (23.03 stalks), panicle length (55.42 cm), 1,000 grain weight (24.84 grams), and plant height. ABC Mix nutrients contain a complete and balanced composition of essential elements, enabling them to meet the growth requirements of rice plants during both the vegetative and reproductive phases, leading to more optimal production. Meanwhile, flowering age in all treatments exceeded 80 days after transplanting (DAT). This is presumed to be due to a delay in the application of GA3, as the activation of floral meristem genes requires approximately five days after GA3 is applied. Additionally, GA3 plays a role in cell elongation, which affects plant height and may contribute to delayed initiation of flowering.